2009
DOI: 10.1179/joc.2009.21.6.611
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance among Gram-Positive Bacteria Isolated in Latin American Hospitals

Abstract: Antimicrobial resistance patterns of the most frequently isolated Gram-positive bacteria in selected Latin American hospitals were evaluated under the auspices of the SENTRY Antimicrobial Surveillance Program. The strains were consecutively collected (one per patient) between January 2003 and December 2008 and tested by reference broth microdilution methods at the monitoring central laboratory (JMI Laboratories, North Liberty, Iowa, USA). A total of 12,324 Gram-positive cocci were analyzed. The organisms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
(20 reference statements)
1
12
0
6
Order By: Relevance
“…Results of a recent SENTRY study revealed a recognizable change of vancomycin resistance rates among clinical enterococcal isolates from participating Latin American countries/hospitals increasing from 5 to 15.5% within 6 years (between 2003 and 2008). The most significant increase was demonstrated for Brazil with VRE rates rising from 7 to 31% (Sader et al, 2009). Considering that the majority of enterococcal isolates is E. faecalis which mainly remained susceptible to vancomycin, the increase of vancomycin resistance among E. faecium isolates seems even more dramatic based on the numbers specified.…”
Section: Latin Americamentioning
confidence: 95%
“…Results of a recent SENTRY study revealed a recognizable change of vancomycin resistance rates among clinical enterococcal isolates from participating Latin American countries/hospitals increasing from 5 to 15.5% within 6 years (between 2003 and 2008). The most significant increase was demonstrated for Brazil with VRE rates rising from 7 to 31% (Sader et al, 2009). Considering that the majority of enterococcal isolates is E. faecalis which mainly remained susceptible to vancomycin, the increase of vancomycin resistance among E. faecium isolates seems even more dramatic based on the numbers specified.…”
Section: Latin Americamentioning
confidence: 95%
“…However, the authors did not identify the VRE species or genotypes 19 . According to more recent data from the SENTRY Program, the percentage of VRE in Brazil increased from 6.9% in 2003 to 31.1% in 2008 and the majority (68.5%) of these isolates were E. faecium 20 . These VRE rates are much higher than that observed in other Latin America countries and in our hospital.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…ARMed çalışmasında en düşük MRSA oranları Lübnan (% 12), Tunus (% 18) ve Fas'da (% 19); en yüksek MRSA oranları Ürdün (% 56), Kıbrıs (% 55) ve Mısır'da (% 52) saptanmış, Türkiye'deki direnç % 39 olarak bildirilmiştir (2) . SENTRY antimikrobial sürveyans çalışmasında 12,324 Gram pozitif suşun % 53'ü kan kültürün-den izole edilmiş ve metisilin direnci % 40 oranında gözlenmiştir (14) . Gales ve ark.…”
Section: Discussionunclassified
“…Sader ve ark. (14) MRSA izolatlarında eritromisin ve klindamisin direncini sırasıyla % 90 ve % 84 oranlarında saptamışdır.…”
unclassified
See 1 more Smart Citation